+0  
 
0
109
1
avatar

If (2x - 3y)^2 = 4 and xy = -5, what is the value of 4x^2 + 9y^2?

 May 8, 2022
 #1
avatar+9461 
+1

We want 4x^2 + 9y^2, which is actually just (2x)^2 + (3y)^2, and the first equation looks kinda like it so we may try to expand the left-hand side of the first equation.

 

Using the identity (a - b)^2 = a^2 - 2ab + b^2,

\(\begin{array}{rcl} (2x - 3y)^2 &=& 4\\ (2x)^2 - 2(2x)(3y) + (3y)^2 &=& 4\\ 4x^2 - 12xy + 9y^2 &=& 4 \end{array}\)

 

We are almost there. The term we don't want is -12xy, but we know exactly what the value of -12xy is. Can you proceed from here?

 May 8, 2022

27 Online Users

avatar
avatar